Peningkatan Hasil Belajar Mail Merge Menggunakan Model Project Based Learning Pada Siswa Kelas X - Yanti Hermawati Puji Rahayu (Faktor : Jurnal Ilmiah Kependidikan, 2023)
The initial data mail merge learning skills students class X with very good criteria is only 14 from 34 people, so the outcomes average value reaches only 72.50. The purpose of study is to increase students' mail merge skills through the application of the Project Based Learning (PjBL) model. This research was conducted through classroom action consisting of two cycles, each cycle consisting of two meetings. The stages of each cycle are: planning, implementation, observation and reflection. Data on students' mail merge skills were taken using an instrument of learning skills observation sheets on indicators: (1) reading the steps for making mail merges, (2) designing mail merge letters, (3) making master letters, (4) creating data source tables, (5) combining the master letter and data source using the mailings menu in Microsoft Word. The results showed that the skills of students with very good criteria increased by 15 students from 14 students in cycle 1 becomes 29 students in cycle 2. Learning outcomes showed an increase of 13.62 from an average 73.26 in cycle 1 to 86.88 in cycle 2. Based on data, it can be concluded that the application of PjBL in learning mail merge can improve student learning outcomes.